Pengaruh Literasi Keuangan terhadap Manajemen Keuangan Pribadi Mahasiswa Rumpun Ekonomi: Effect of Financial Literacy on Personal Financial Management of Economics Group Students - Lia, Sena Taliya; Gumilar, Gugum; Sartika, Sri Hardianti (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The issue addressed in this study is the low level of students' ability to manage personal finances. Many students from the Economics cluster at Siliwangi University, particularly those from the 2021 and 2022 cohorts, do not have a monthly budget, do not regularly record their financial transactions, are inconsistent in saving, and experience doom spending behavior due to low financial literacy. This study aims to determine the influence of financial literacy on personal financial management among students. A quantitative approach with a survey method was employed. The population consisted of 2,142 students, and a simple random sampling technique was used to obtain 326 respondents. Data were collected through a questionnaire. The results showed that financial literacy has a significant effect on students' personal financial management.